1993
DOI: 10.1002/jlb.54.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Overview of spaceflight immunology studies

Abstract: The effects of spaceflight and analogues of spaceflight are discussed here and in nine accompanying articles. In this summary we present spaceflight studies with human subjects, animal subjects, and cell cultures and we review ground-based systems used to model the observed effects of spaceflight on the immune system. Human paradigms include bed rest, academic or psychological stress, physical stress, hypobaric or high altitude stress, and confinement. Animal models include antiorthostatic and orthostatic susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…The effects of spaceflight on the immune system are not caused simply by physical and psychological stress but may also be directly affected by microgravity (Martinelli et al, 2009). Previous studies have shown that microgravity and SMG can affect both the proliferation and viability of lymphocytes, which suggests that their effects occur at the cellular level (Meehan et al, 1992;Taylor, 1993;Cooper and Pellis, 1998;Sastry et al, 2001;Martinelli et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of spaceflight on the immune system are not caused simply by physical and psychological stress but may also be directly affected by microgravity (Martinelli et al, 2009). Previous studies have shown that microgravity and SMG can affect both the proliferation and viability of lymphocytes, which suggests that their effects occur at the cellular level (Meehan et al, 1992;Taylor, 1993;Cooper and Pellis, 1998;Sastry et al, 2001;Martinelli et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, confinement of the crew during flight can and has resulted in the transfer of microorganisms between crew members (13,26,27). All of these factors are known to affect many physiological parameters of the astronauts, including the immune system (12,17,20,31,32,41). Their effects include decreased functions of cells of the innate immune system, including neutrophils (14, 36), monocytes (15), and NK cells (17,21).…”
mentioning
confidence: 99%
“…A number of examples exist of test panels that are in use or have been recommended by government agencies and private-sector scientists involved in immunologic field assessment (Beisel and Talbot, 1985;Taylor, 1993 . The outcomes of this workshop included recommendations for a panel of tests for assessment of immune deficiency as well as factors that must be considered in the design of field studies.…”
Section: Assessment Techniquesmentioning
confidence: 99%
“…However, assays of whole-blood cytokine production (De Rijk et al, 1996 may provide a more sensitive method than was available previously to measure immune changes associated with exercise and stress. The choice of techniques will depend on the investigator's resources and the availability and accessibility of tissue, blood, or biological fluid to be assayed.A number of examples exist of test panels that are in use or have been recommended by government agencies and private-sector scientists involved in immunologic field assessment (Beisel and Talbot, 1985;Taylor, 1993 . The outcomes of this workshop included recommendations for a panel of tests for assessment of immune deficiency as well as factors that must be considered in the design of field studies.…”
mentioning
confidence: 99%